Mapping a Decade of Bullying Research in Counseling: A Bibliometric Analysis Using VOSviewer - Pasmawati, Hermi; Afriyati, Vira; Astarini, Dilla; Awlawi, Addahri Hafidz; Azis, Akhmad Rifki (KONSELOR, 2025)
This study presents a bibliometric analysis of research trends on bullying within the counseling field, based on 174 peer-reviewed articles indexed in the Scopus database between 2014 and 2024. Bibliometric techniques—including keyword co-occurrence mapping, co-authorship network analysis, and citation tracking—were conducted using VOSviewer to identify dominant themes, influential authors and journals, and patterns of scholarly collaboration. The analysis revealed eight major keyword clusters, primarily centered around childhood adversity, mental health outcomes, and counseling-based intervention strategies. Prominent contributors included authors such as Espelage, D.L., and journals such as Children and Youth Services Review, School Psychology International, and the Journal of Counseling & Development. The United States, the United Kingdom, and Australia emerged as the most productive countries, with medicine, psychology, and social sciences dominating the subject areas. Research output peaked in 2021 and 2023. Despite the overall growth in scholarly interest, topics such as cyberbullying and anti-violence education remained underrepresented, indicating important gaps for future exploration. These insights offer a clearer understanding of the field’s evolution and provide valuable direction for researchers, practitioners, and policymakers committed to advancing bullying-related interventions in counseling contexts.